2020
DOI: 10.1097/spc.0000000000000498
|View full text |Cite
|
Sign up to set email alerts
|

Does circadian rhythm influence gastrointestinal toxicity?

Abstract: Purpose of review The current review outlines the existing research on the impact of circadian rhythm on gastrointestinal toxicity associated with cancer treatment and explores clinical evidence for utilizing circadian-based approaches in addressing gastrointestinal symptoms such as nausea, vomiting, diarrhea, mucositis, and hepatotoxicity. Recent findings Recent evidence highlights circadian control of gastrointestinal physiology of appetite, digestion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…has not yet been reported, the in uence of circadian rhythm on gastrointestinal toxicity due to other cancer therapies (e.g., chemotherapy) is under investigation (as reviewed in 10 ). Nonetheless, it has been reported that NPAS2 might affect another common opioid side effect, i.e., the alteration of the sleep-wake cycle.…”
Section: Discussionmentioning
confidence: 99%
“…has not yet been reported, the in uence of circadian rhythm on gastrointestinal toxicity due to other cancer therapies (e.g., chemotherapy) is under investigation (as reviewed in 10 ). Nonetheless, it has been reported that NPAS2 might affect another common opioid side effect, i.e., the alteration of the sleep-wake cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of circulating pro-inflammatory cytokines, induced by both cancer processes and anticancer treatments, which can alter the circadian coordination centrally, have been indeed shown to be associated with the clustering of fatigue and anorexia in cancer patients. 41 Circadian disruption could also account for digestive complaints, 101 sleep troubles, 102 and altered metabolism. 103 Thus, the accurate evaluation of circadian function through remote monitoring of cancer patients 83 could represent a biomarker of physiological and behavioral alteration, 75 a surrogate of symptom burden and of subjective complaints, 100 , 104 , 105 as well as a potential novel target of intervention, both pharmacological and behavioral.…”
Section: Circadian Phenotypingmentioning
confidence: 99%
“…Additionally, another broader therapeutic approach could involve the use of circadian-based anticancer treatments, which accounting for temporal oscillations in pharmacological and physiological determinants of drug effects aim at reducing toxicity and enhancing activity (101). However, despite the extensive experimental evidence showing a marked impact of time of administration of various class of anticancer drugs on their tolerance or efficacy (102), and trials supporting its clinical relevance as well (103,104), cancer chronotherapy is not yet routinely applied (105). Nonetheless, translational research avenues identifying determinants of personalised and precise chronotherapeutic schedules warrant dedicated novel trials to be developed with timing of drug administration as a fundamental aspect to optimize and improve patient outcomes (63).…”
Section: Future Directionsmentioning
confidence: 99%